Efektivitas SEMA No. 3 Tahun 2023 Dalam Menekan Angka Perceraian 2023-2025 Studi Di Pengadilan Agama Mataram Kelas IA - Farobi Syahuda, Hammad; Hariyani, Dwi Yulia; Firdaus, Nurul (Al-Ahwal Al-Syakhsiyyah: Jurnal Hukum Keluarga dan Peradilan Islam, 2026)
This study aims to analyze the effectiveness of the implementation of the Supreme Court Circular Letter (SEMA) Number 3 of 2023 in reducing divorce rates at the Mataram Religious Court Class 1A, particularly divorces filed on the grounds of continuous disputes and quarrels. This research employs an empirical juridical method with a descriptive-analytical approach. Primary data were obtained through interviews with judges, court clerks, and court officials, as well as documentation of divorce case data at the Mataram Religious Court. Secondary data were collected through a literature review of relevant laws and regulations, books, and academic journals. The data were analyzed using Lawrence M. Friedman’s theory of legal effectiveness, which emphasizes three elements of the legal system: legal substance, legal structure, and legal culture. The results show that the implementation of SEMA No. 3 of 2023 at the Mataram Religious Court is carried out through two main stages: the filtering and educational stage at the One-Stop Integrated Service (PTSP) before case registration, and the case examination stage during court proceedings by the panel of judges. Empirically, the policy indicates a decrease in the percentage of divorces based on continuous disputes and quarrels in 2025, although the overall divorce rate remains relatively high. From the perspective of legal effectiveness theory, this policy can be considered relatively effective in terms of legal substance and legal structure due to clear regulatory provisions and proper implementation by judicial officials. However, its effectiveness is still constrained by the legal culture of society, where many litigants tend to seek quicker divorce processes and have limited understanding of the applicable legal provisions.